Nitrogen Balance and Nitrogen Use Efficiency (NUE) Atlas from Rice, Wheat, Maize and Soybean at Global Scale - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
We have 0.5 degree database on N input accounting all sources (synthetic fertilizers, animal manure, crop residues, soil mineralization, atmospheric deposition and N fixation). We are now working on N output using gridded data on crop harvest area and production with university of Minnesota, which will follow NUE atlas development.